Determinación del efecto de seis productos biorracionales sobre Moniliophthora perniciosa, agente causal de escoba de bruja en cacao (Theobroma cacao L. ) - Espinoza Carranza, Jonatham Joseph (2012)
The witches' broom, caused by pernicious Moniliophthora. This disease attacks the cocoa generating losses of 40 to 70% of production, without taking into account the reduction of plant vigor for the attack on shoots, internodes and bearing flowers and fruits, the best control for this disease is the integrated crop management, including annual pruning, proper fertilization, weekly removal of diseased fruits and application of protective chemicals and the use of biorational, current agricultural demand reduction of chemical pesticides and the introduction of sustainable systems, one of whose alternative is to use biorational agents for the control of pests and diseases that could be a promising strategy to control. This study was conducted at the Experimental Station of Tropical Pichilingue INIAP and aimed to study the efficacy of six biorational products for handling Witches' broom (M. perniciosa) in cocoa (Theobroma cacao L.) at laboratory and greenhouse. Biorational products studied were: TRICHOEB 5WP (soil conditioner), ECOFLORA (biological Conditioner), ECOFUNGI (mycorrhizal inoculant), 3b112 SC (Inhibitor of fungal sporulation) and Bankit (systemic fungicide). In the greenhouse trial dry Brooms level variables were measured number of basidiocarps before inoculation and number of basidiocarps after inoculation in the laboratory test was measured radial growth of pathogenic fungus and physical reaction at the level of seedlings was studied incubation period (Pi) and incidence. For the first two trials used a completely randomized design (DCA) and the third trial used a completely randomized design with factorial arrangement of 2 x 6 with 10 observations. For the difference of treatment means, we used the Tukey's multiple range test at 95% probability. In the first trial stromaticum, Bankit Trichoeb and significantly reduced production of both basidiocarps 15 as at 30 days. In the second trial and stromaticum Bankit differ statistically from the other study treatment inhibiting radial growth of the pathogen. In the third experiment being Bankit, Stromatium Trichoeb and those with the best results in the variable incubation period (IP) and the variable incidence stromaticum, Bankit and Trichoeb still located at the top.